COVID-19 infection and decline in outdoor activities associated with depression in older adults: A multicenter study in Vietnam. - Huan Thanh Nguyen; Thien Hoang Le; Chanh Cong Nguyen; Thanh Dinh Le; Tan Van Nguyen (PLoS ONE, 2023)
Background The coronavirus disease (COVID-19) pandemic has caused a serious global communicable disease burden. Although COVID-19 and its policy responses have significantly influenced older adults, the impact of COVID-19 on depression in the older population is not fully understood. We aimed to investigate whether a history of COVID-19 infection and a decline in outdoor activities during the COVID-19 pandemic were associated with depression among older adults in Vietnam. Methods This multicenter cross-sectional study was conducted on 1,004 outpatients (aged ≥60 years; mean age 70.8 ± 7.3 years; men, 33.0%) visiting three hospitals for a comprehensive geriatric assessment between November 2021 and July 2022. Depression over the past week was evaluated using the 15-item Geriatric Depression Scale. History of COVID-19 infection and decline in outdoor activities were included as binary variables. We adjusted these two factors with sociodemographic and geriatric variables and comorbidities using a logistic regression analysis in separate models. Results A total of 156 participants (15.5%) experienced depression. The proportion of mild, moderate, and severe depressive symptoms was 14.1%, 44.9%, and 41.0%, respectively. In the multivariate model, decline in outdoor activities (odds ratio [OR] 17.2, 95% confidence interval [CI] 9.15-32.2, p <0.001) and history of COVID-19 infection (OR 2.22, 95% CI 1.28-3.84, p = 0.004) were associated with depression. Additionally, we found that age ≥ 75 years, female sex, being underweight, limitations in functional status, poor sleep quality, and stroke were associated with depression. Of the associated factors, decline in outdoor activities had a moderate strength of association with depression (r = 0.419), while each of the remaining factors had a weak strength of association. Conclusions COVID-19 had a direct and indirect impact on depression in older adults, reflecting an association between both a history of COVID-19 infection and a decline in outdoor activities during the COVID-19 pandemic and depression in the older population.